PENGARUH PROFITABILITAS DAN AKTIVITAS TERHADAP HARGA SAHAM PT. GUDANG GARAM INDONESIA Tbk PADA TAHUN 2012 - 2021 - Wasim, Bisyarah; Nuryani, Anum (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Return On Assets (X1) and Total Asset Turn Over (X2) on Share Prices (Y) at PT. Gudang Garam Indonesia Tbk for the 2012-2021 period, partially or simultaneously. The method used in this research is to use a quantitative approach with several test models, including Descriptive Statistical Analysis, Classic Assumption Test, Regression Analysis, Hypothesis Testing and Determination Coefficient (R2) using SPSS version 26 software. Return Variable On Asset (X1) has a significant effect on Share Price (Y). Meanwhile, the Total Asset Turn Over variable has no significant effect on share prices. For Return On Assets, it shows a significance value (0.029 < 0.05) and the results of the t- test show results greater than ttable (2.738 > 2.306), so it can be concluded that Ha1 is accepted and means that there is a significant effect between Return On Assets (X1) on Share Prices ( Y). The research results for Total Asset Turn Over show a significance value of 0.273 > 0.05 and the results of the t- test show results that are smaller than ttable (1.190 > 2.306), so it can be concluded that H2 is rejected and means there is no influence and is not significant between Total Asset Turn Over (X2) to Share Price (Y). Then simultaneously the Return On Asset and Total Asset Turn Over variables have no effect and are not significant on Stock Prices with the result being that the Fcount value is smaller than Ftable, which is the same as the table 3.980 < 4.74 with a significance level of 0.070 < 0.05, then it can be said that H3 is rejected.